Evolução Parque Automóvel e como é que ele afeta o setor de serviços rápidos - Soares, Diogo Souto (2023)
Multiple changes are occurring in the automotive sector, this thesis presents some aspects of the new era of mobility and presents the implications they will have on the automotive sector. This dissertation aims to show the evolution of the sector and how it will affect the aftermarket sector. Over the next decade, several trends threaten to constrain growth and shrink industry profit margins. Therefore, we will try to respond to the following topics: The evolution of mobility in recent years; Study the impact that new types of vehicles (electric, hybrid, others) have on the aftermarket sector and understand how the car fleet is changing at a Portuguese national level; Correlate the mobility trend with new data management and processing methodologies. It will also be demonstrated how data was collected to analyze the occupancy rate of a sample of workshops from a network in Portugal and how the forecast study for occupancy rates in the following months was carried out. A discussion of the highlighted topic is also presented, where we address the topic of future profitability of workshops in the quick service sector. Finally, we present a conclusion in which the limitations suffered during this work are also presented and future work is identified.